ANALISIS PENGARUH STORE IMAGE, PRICE ACCURACY (HARGA), DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK GROCERY DI MODEREN MARKET MELALUI POINT OF PURCHASE (POP) SEBAGAI VARIABEL INTERVENING : Studi Pada Carrefour Plaza Ambarrukmo Yogyakarta - Suhartono Suhartono (Universitas Sarjanawiyata Tamansiswa, 2022)
This research aimed to determine the effect of the marketing mix, specifically the analysis of the effects of store image, price accuracy (price), and product completeness on grocery products purchase decisions in the modern market through point of purchase (pop) as intervening variables. This research used 200 respondents as samples by applying a purposive sampling approach of which the sampling method based on certain considerations. The data collection method applied is a questionnaire using a Likert scale. Based on the test result, it claimed that store image, product completeness have a positive and significant effect on the point of purchase, while price accuracy had not. Store image, price accuracy, product completeness and point of purchase also had a positive and significant effect on the purchasing decisions. With path analysis, the magnitude of the indirect effect was greater than the direct effect so that the point of purchase was able to mediate between the effects of store image, price accuracy, and product completeness on purchase decisions.